The participial oblique, a verb mood found only in Nunivak Central Alaskan Yup'ik and in Siberian Yupik - Jacobson, Steven (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractNunivak Island has the most divergent dialect of Central Alaskan Yup'ik Eskimo, the language of southwestern Alaska. Lexical and phonological divergences have been discussed elsewhere. This paper discusses the form and function of the “participial oblique” verb mood found in Nunivak—but not in other Central Alaskan Yup’ik dialects—and in Central Siberian Yupik Eskimo, the language of St. Lawrence Island Alaska and the tip of Chukotka. Discussed also are differences between the Chukotkan form of the mood and that of St. Lawrence Island, the mood’s presence in Naukan Yupik, and a probable “missing link” participial construction in other Central Alaskan Yup’ik dialects.